TOTAL FLAVONOID DAN AKTIVITAS PENANGKAPAN RADIKAL BEBAS DARI EKSTRAK ETANOLIK DAUN DAN BUAH MENGKUDU - Wigati, Dyan; Koko Pratoko, Dwi (Jurnal Farmasi (Journal of Pharmacy), 2016)
Morinda citrifolia L. is a plant widely used as a traditional medicine that rich of flavonoid contents. The aims of this study were to determined the total flavonoid content and free radical scavenging activity ethanolic extract of M. citrifolia L. leaves and fruits in order to find a new antioxidant sources. Total flavonoid contents were determined by aluminium chloride colorimetric method. The free radical scavenging activity of the extract ethanolic of M. citrifolia L. leaves and fruits were measured in vitro by 2,2-diphenyl-1-picrylhadrazyl (DPPH) assay. The total flavonoid contents of M. citrifolia L. leaves extract (23.05 ± 0.77 mg RE/g extract) were found significantly higher than fruits extract (18.81 ± 1.10 mg RE/g extract). Free radical scavenging activity of ethanolic extract of M. citrifolia L. leaves and fruits show that IC50 values of the leaves extract (49.09 ± 0.40 µg/mL) higher than IC50 values of the fruits extract (384.08 ± 2.29 µg/mL). The t-test result show a significant difference between fruits extract and leaves extract of the total flavonoid and free radical scavenging activity (p < 0,05). Data from present result revealed that both of M. citrifolia L. leaves and fruits extract act as an antioxidant agent due to its free radical scavenging activity.